Exploring Neural Efficiency in Multiple Sclerosis Patients during the Symbol Digit Modalities Test: A Functional Magnetic Resonance Imaging Study - Fittipaldi, María Sol (2017)
Background: Reduced information-processing speed (IPS) is a primary cognitive deficit of multiple sclerosis (MS) patients. The neural efficiency hypothesis describes an inverse relationship between cognitive performance in a task and the amount of cognitive resources devoted to it. Previous studies have shown that the neural efficiency hypothesis provides an appropriate framework to explore cognitive dysfunction in neurological patients. Objective: The aim of this study was to explore the neural efficiency hypothesis regarding IPS capabilities in cognitively preserved MS patients. Methods: 16 MS patients and 17 healthy controls (HCs) were enrolled and neuropsychologically assessed. All participants also performed a functional magnetic resonance imaging (fMRI)-adapted version of the Symbol Digit Modalities Test (SDMT) at different interstimulus intervals (ISI: 1.5, 2, and 2.5 s). Results: MS patients only displayed lower SDMT performance when the ISI was set at 1.5 s. However, MS patients´ normal SDMT performance at larger ISIs was achieved at the cost of increased brain activation, hence revealing that they were less cognitively efficient than the HCs. Regression analyses confirmed this conclusion by showing an opposite relationship between SDMT performance and the amount of neural resources recruited in the HC and MS groups. Thus, while a positive relationship between both variables was observed in MS patients, this correlation was negative for the HC group. Conclusions: MS patients require more cognitive resources than HCs to achieve a normal SDMT performance, then revealing that they are less efficient regarding IPS capabilities.